MENGENAL RISALAH NUR KARYA SAID NURSI DAN METODOLOGI PENAFSIRANNYA - Syauqi, Muhammad Labib (MAGHZA, 2017)
An interpretation is a social product and the work of ordinary people, which is inappropriate to be considered a sacred thing and also it is not anti to be criticized. Bediuzzaman Said  Nursi interpreted the Qur'an based on the context at that time. Nursi was not only reading the Qur'an from the limited text but was also understanding it relied on the belief of the correctness of the religious texts by using rational thinking approach. This paper will try to explore the methodology used by Nursi in greater depth by examining various Nuri’s quotations of interpretation results in his masterpiece, the Risa>lah al-Nu>r. The methodology is closely related to the result of his thinking, in order to understand the author's line of thought comprehensively.